1990
DOI: 10.1037/0278-7393.16.4.656
|View full text |Cite
|
Sign up to set email alerts
|

Memory for odors and odor names: Modalities of elaboration and imagery.

Abstract: This study examined memory for common odors and odor names that were encoded with visual, verbal, and olfactory elaborations. In the first experiment, subjects elaborated olfactory stimuli by processing a picture of the odor's source, a name for the odor, or both. Two control groups were also included: One group was presented only with the odors, and another group was presented only with odor names. One week later, all subjects were given both a free recall test of odor names and an olfactory recognition test.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
76
1
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(93 citation statements)
references
References 39 publications
15
76
1
1
Order By: Relevance
“…In line with the present study, Cronin-Golomb, Gabrieli, and Keane (1996) failed to show any difference between ipsi-and contralateral testing for visual word-stem completion priming. Lyman and McDaniel (1990) made a strong case for dual perceptual and semantic encoding in memory for odors. Semantic encoding of odors, assessed by the quality of names assigned to stimuli, accounts for a considerable amount of variance in performance in recognition memory (Larsson, 1997;Murphy, Cain, Gilmore, & Skinner, 1991;Rabin & Cain, 1984).…”
Section: Ipsi-versus Contralateral Testingmentioning
confidence: 99%
“…In line with the present study, Cronin-Golomb, Gabrieli, and Keane (1996) failed to show any difference between ipsi-and contralateral testing for visual word-stem completion priming. Lyman and McDaniel (1990) made a strong case for dual perceptual and semantic encoding in memory for odors. Semantic encoding of odors, assessed by the quality of names assigned to stimuli, accounts for a considerable amount of variance in performance in recognition memory (Larsson, 1997;Murphy, Cain, Gilmore, & Skinner, 1991;Rabin & Cain, 1984).…”
Section: Ipsi-versus Contralateral Testingmentioning
confidence: 99%
“…The advantage of this method is that it allows us to ask directly about the most salient aspect of imagery-its phenomenal quality. Needless to say, such reports may suffer from various biases (see Richardson, 1999); however, several authors have reported positive correlations between such self-reports and measures of olfactory imagery not reliant on this form of measure (e.g., Bensafi et al, 2005;Djordjevic, Zatorre, Petrides, & Jones-Gotman, 2004;Lyman & McDaniels, 1990). More generally, in the visual imagery literature, where this relationship has been studied extensively, a modest but appreciable correlation (r .27) has been obtained between these variables, across studies (McKelvie, 1995).…”
mentioning
confidence: 99%
“…Second, in earlier studies, access to verbal labels at the time of study did not affect subsequent odor recognition performance (Engen and Ross 1973;AyabeKanamura et al 1997). Although verbal elaboration about odors at the time of study can sometimes facilitate subsequent recognition (Lyman and McDaniel 1990), it is thought that odors are typically perceived as unitary items without a strong verbal link. That is, the association between odors and their verbal labels is ordinarily rather weak (Engen 1987;Lyman and McDaniel 1990).…”
mentioning
confidence: 99%
“…Although verbal elaboration about odors at the time of study can sometimes facilitate subsequent recognition (Lyman and McDaniel 1990), it is thought that odors are typically perceived as unitary items without a strong verbal link. That is, the association between odors and their verbal labels is ordinarily rather weak (Engen 1987;Lyman and McDaniel 1990). Third, in an earlier study involving the same odors (Levy et al 2003), the olfactory memory span attained by controls (7.9) was about the same as the memory span for difficult-to-verbalize designs (8.6) and much less than the memory span for line drawings of nameable objects (21.1).…”
mentioning
confidence: 99%